Complementary and alternative medicine in the (symptomatic) treatment of acute tonsillitis in children: A systematic review - Rebecca Büttner; Melanie Schwermer; Thomas Ostermann; Alfred Längler; Tycho Zuzak (Complementary Therapies in Medicine, 2023)
Background: Acute tonsillitis (including tonsillopharyngitis) in childhood is a common disease with a peak of illness in school-age. Most of these cases have a viral origin and antibiotic therapy is not indicated, therefore, effective symptomatic therapy is required. For this reason, complementary, alternative and integrative medicine therapies might be a solution. Objective: The aim of this review is to demonstrate study status of such therapies. Methods: The databases PubMed, Cochrane Library, OVID, CAMbase, CAM-QUEST® and Anthromedics were systematically screened for studies investigating complementary, alternative and integrative therapy approaches in paediatric cohorts. Studies were analyzed by therapy approach, study design, cohort and outcome, using the PRISMA 2020 checklist. Results: The systematic literature search resulted in 321 articles. Five publications corresponded to the search criteria and were assigned to the following specific therapeutic categories: herbal medicine (3), homeopathy (1) and ayurvedic medicine (1). Clinical trials were found for the herbal compounds BNO 1030 (Impupret®) and EPs® 7630 (Umckaloabo), the homeopathic complex Tonzolyt® and the ayurvedic medicine Kanchnara-Guggulu and Pratisarana of Tankana‑Madhu. Antimicrobial effects of essential oils and carvacrol as single agents as well as in combination with erythromycin were analysed in an in vitro study. Conclusion: Clinical studies indicate an improvement of symptoms and a good tolerability of all investigated remedies of complementary, alternative and integrative medicine in the treatment of tonsillitis in childhood. Nevertheless, quality and quantity of the studies were insufficient to make a reliable conclusion regarding effectiveness. Therefore, more clinical trials are urgently needed to achieve a meaningful result.